2011
DOI: 10.1515/form.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

On some multiplicity and mixed multiplicity formulas

Abstract: This paper gives the additivity and reduction formulas for mixed multiplicities of multi-graded modules M and mixed multiplicities of arbitrary ideals, and establishes the recursion formulas for the sum of all the mixed multiplicities of M. As an application of these formulas we get the recursion formulas for the multiplicity of multi-graded Rees modules.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The notion of filterregular sequences was introduced by Stuckrad and Vogel in [17] (see [2]). The theory of filter-regular sequences became an important tool for studying some classes of singular rings and has been continually developed (see, for example, [2,8,20,29,31] (ii) Let a ∈ S i . Since the following exact sequence…”
Section: Filter-regular Sequences and Mixed Multiplicity Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The notion of filterregular sequences was introduced by Stuckrad and Vogel in [17] (see [2]). The theory of filter-regular sequences became an important tool for studying some classes of singular rings and has been continually developed (see, for example, [2,8,20,29,31] (ii) Let a ∈ S i . Since the following exact sequence…”
Section: Filter-regular Sequences and Mixed Multiplicity Systemsmentioning
confidence: 99%
“…Using different sequences, one can express mixed multiplicities of ideals in terms of the Hilbert-Samuel multiplicity. For instance, in the case of n-primary ideals, Risler-Teissier [19] in 1973 showed that each mixed multiplicity is the multiplicity of an ideal generated by a superficial sequence and Rees [14] in 1984 proved that mixed multiplicities are multiplicities of ideals generated by joint reductions; for the case of arbitrary ideals, Viet [23] Note that [23] defines weak-(FC)-sequences in the condition I √ Ann R N (see, for example, [5,6,13,24,25,26,28,30,31]). In Definition 4.12, we omitted this condition.…”
Section: Consequently By Corollary 311(ii) We Obtain (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that this theorem does not hold in general if one omits the assumption k 1 + · · · + k s < h (see Remark 3.5). Our approach, which is based on the results in [18] and [24], links the multiplicity of (FC)-sequences in [18] and the multiplicity of joint reductions via our studies on these sequences (see Proposition 2.3 and Lemma 2.5). As an application of the main theorem, we interpret mixed multiplicities as Hilbert-Samuel multiplicities of Rees's superficial sequences (see Remark 3.4) and recover Rees's theorem in [12,Theorem 2.4] (see Corollary 3.6).…”
Section: Imentioning
confidence: 99%
“…In a recent paper [20], by a new approach, the authors gave the additivity and reduction formulas for mixed multiplicities of multi-graded modules and mixed multiplicities of arbitrary ideals; and they also showed that mixed multiplicities of arbitrary ideals are additive on exact sequences.…”
Section: Introductionmentioning
confidence: 99%